PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH SERVANT LEADERSHIP TERHADAP KOMITMEN ORGANISASI - dwiki, I Made; Riana, I Gede (E-Jurnal Manajemen, 2018)
The purpose of this study was to examine the role of job satisfaction in mediating the influence of servant leadership on employee organizational commitment by using the slovin formula of samples taken as many as 75 employees, through path analysis technique. Based on the analysis results can be concluded that servant leadership has a positive effect on job satisfaction. Job satisfaction has a positive effect on organizational commitment. Servant leadership has a positive influence on organizational commitment. Job satisfaction mediates the effect of servant leadership on organizational commitment. Implications that can be given to corporate leaders through the application of servant leadership can maintain a sense of togetherness in the company with mutual respect-respect between superiors and subordinates and provide direct rewards for employees who have a positive contribution for the progress of the company. Evaluate job satisfaction perceived by employee related salary amount given to fit with work load in each part. Enhance commitment attitude together by instilling a sense of togetherness so that employees have the desire to come to achieve the vision of the company's mission to stay in the company without thinking of other things.   Keywords : servant leadership, job satisfaction, organizational commitment